Analysis of Technological State Implementation: Case Study of President Jokowi's Nickel Downstream Policy - Khairurrizqo, Khairurrizqo; Millata, Chanifia Izza (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Indonesia is currently the country with the worlds number one Nickel reserves, according to USGS (United States Geological Survey) records in 2021. Nickel is strategically valuable due to its high demand as a raw material for electric car batteries. However, until 2019, Indonesia exported Nickel only as low-value ore. Then, in 2020, the government banned the export of nickel ores by increasing the number of processing smelters to create more added value, called the downstream policy. Downstream policy requires solid political commitment to improve innovation and Nickel processing technology to improve added value. This study will analyze the commitment of the governments technology and innovation policies to improve the value-added of its natural resources using the Technological State implementation. Indicators of technological state implementation include the governments goal to achieve technological supremacy over other countries, a high level of autonomy for technological institutions, and state institutions that serve to develop new technological advancements. This study uses a qualitative research method with a descriptive approach. Descriptive research was selected to explain the background of the Nickel Downstream policy in the era of President Jokowi and the Technological State analysis, which is needed to improve the added value of natural resources. The results showed that the Nickel Downstream policy needed sufficient technological state implementation from the government to improve its added value.